Buchrezension zu: The Voices of Nature - Marina Scheumann (BIOspektrum, 2024)

Introduction to the Special Issue Celebrating the Life and Work of Elke Zimmermann - Ute Radespiel; Marina Scheumann (International Journal of Primatology, 2022)

Third-party vocal intervention in the proboscis monkey (Nasalis larvatus) - Marina Scheumann; Kathrin M. Röper; Senthilvel K. S. S. Nathan; Benoit Goossens (International Journal of Primatology, 2022)
Vocal intervention is a triadic social interaction, where a third party responds vocally to a conflict between group members, minimizing the costs of aggression in response to the intervention. Because there is little information on vocal third-party intervention in nonhuman mammals, we investigated whether adult male proboscis monkeys use the bray vocalization as a vocal third-party intervention signal to intervene in intragroup conflicts. First, we audio-recorded 1,811 vocalizations from 17 free-ranging proboscis monkey groups in the Lower Kinabatangan Wildlife Sanctuary, analyzing 378 vocal responses of the adult male to agonistic vocal exchanges (shrieks) of group members. Second, we video- and audio-recorded five habituated groups in the Labuk Bay Proboscis Monkey Sanctuary investigating the context of these vocalizations and the conflict dyads evoking vocal support. We found that adult males of one-male/multifemale groups mainly uttered bray vocalizations, whereas females, immatures, and infants uttered shrieks in intragroup conflicts or in response to other animal species. The adult male uttered significantly more often brays after agonistic shrieks than expected based on the overall occurrence of brays. Brays ended 65% of agonistic conflicts, which were accompanied by vocalizations of the conflict partners and occurred more often after conflicts between females than between offspring. This suggests that the bray functions as a vocal third-party intervention signal for intragroup conflict resolution. We suggest that living in the high canopies of the tropical rainforest might restrict direct access to conflict partners and prevent physical intervention, favoring the evolution of the bray as a third-party vocal intervention signal.

Prof. Dr. rer. nat. Elke Zimmermann - Ute Radespiel; Marina Scheumann; Daniel Schmidtke (International Journal of Primatology, 2019)

Sumatran Orangutans and a Yellow-Cheeked Crested Gibbon Know What Is Where - Marina Scheumann; Josep Call (International Journal of Primatology, 2006)